2023
DOI: 10.1002/anie.202312519
|View full text |Cite
|
Sign up to set email alerts
|

A Photolabile Curcumin‐Diazirine Analogue Enables Phototherapy with Physically and Molecularly Produced Light for Alzheimer's Disease Treatment**

Shi Kuang,
Biyue Zhu,
Jing Zhang
et al.

Abstract: The development of Alzheimer's disease (AD) drugs has recently witnessed substantial achievement. To further enhance the pool of drug candidates, it is crucial to explore non‐traditional therapeutic avenues. In this study, we present the use of a photolabile curcumin‐diazirine analogue, CRANAD‐147, to induce changes in properties, structures (sequences), and neurotoxicity of amyloid beta (Aβ) species both in cells and in vivo. This manipulation was achieved through irradiation with LED light or molecularly gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Importantly, we revealed that molecular light from ADLumin‐4, a chemiluminescent compound with Aβ specificity, could be used to replace LED to achieve comparable results in solutions and in cell studies. Lastly, our results suggested that ADLumin‐4 was as efficient as LED irradiation in slowing down the accumulation of Aβs in vivo with transgenic AD mouse models [54,103] . In this study, since both ADLumin‐4 (molecular light) and the photosensitizer (CRANAD‐147) can specifically bind to Aβ aggregates, likely, the high efficiency is because Aβ fibrils can confine both molecular light and the sensitizer within nanometer ranges.…”
Section: Molecular Light For Photo‐therapymentioning
confidence: 67%
See 3 more Smart Citations
“…Importantly, we revealed that molecular light from ADLumin‐4, a chemiluminescent compound with Aβ specificity, could be used to replace LED to achieve comparable results in solutions and in cell studies. Lastly, our results suggested that ADLumin‐4 was as efficient as LED irradiation in slowing down the accumulation of Aβs in vivo with transgenic AD mouse models [54,103] . In this study, since both ADLumin‐4 (molecular light) and the photosensitizer (CRANAD‐147) can specifically bind to Aβ aggregates, likely, the high efficiency is because Aβ fibrils can confine both molecular light and the sensitizer within nanometer ranges.…”
Section: Molecular Light For Photo‐therapymentioning
confidence: 67%
“…Lastly, our results suggested that ADLumin-4 was as efficient as LED irradiation in slowing down the accumulation of Aβs in vivo with transgenic AD mouse models. [54,103] In this study, since both ADLumin-4 (molecular light) and the photosensitizer (CRANAD-147) can specifically bind to Aβ aggregates, likely, the high efficiency is because Aβ fibrils can confine both molecular light and the sensitizer within nanometer ranges. Taken together, our study indicated that molecular light could be as efficient as irradiation from an external light source.…”
Section: Molecular Light For Photo-oxidation Therapymentioning
confidence: 94%
See 2 more Smart Citations
“…Against this background, researchers have endeavored to address these consequential drawbacks by devising a broad range of type I PSs with lower reliance on oxygen, and nanomaterial-engineered PDTs that replenish oxygen within the tumorous environment. Currently, satisfactory results have not yet been achieved. For instance, type II PSs constantly reduce the local oxygen concentration during PDT, ultimately restricting the therapeutic index of PDT in hypoxic solid tumors owing to the absence of local tumor oxygen. From this perspective, monomodal PDT using PSs cannot achieve the aim of fully eradicating tumors. The concentration of nanomaterials accumulated at tumor sites through the enhanced permeability and retention (EPR) effect is estimated to be as high as 0.7%, which raises concerns about oxygen-replenishing nanomaterials’ actual application potential in tumor therapy. , Furthermore, PDT (especially type II PDT) is heavily oxygen-dependent and can exacerbate tumor cell hypoxia, which is precisely what accelerates the release rate of hypoxia-sensitive prodrugs.…”
mentioning
confidence: 99%